Di sản văn hóa Chăm Heritage of Chăm culture - Nguyễn, Văn Kự 1940-; Cao, Xuân Phổ.; Văn Thi Thanh Binh (Hà Nội Nhà xuất bản Thế giới, 2007)
Social life and custom of Chăm people in Vietnam.
Includes bibliographical references (pages 116).
English and Vietnamese.
Keywords: Cham (Southeast Asian people) -- Vietnam -- Social life and customs -- Pictorial works; Cham (Southeast Asian people) -- Vietnam -- Religion -- Pictorial works